The Concept of Beauty Expressed by《漂亮》in Modern Chinese (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This study examines the lexical semantic and pragmatic features of the word “漂亮” in modern Chinese, focusing on its role in expressing the concept of beauty within contemporary linguistic and social contexts. In modern society, language not only serves as a means of communication but also reflects cultural values, aesthetic perceptions, and social attitudes. The word “漂亮” has become one of the most frequently used evaluative adjectives in modern Chinese and is notable for its broad applicability and semantic flexibility.Despite the high frequency of its use, existing linguistic studies have often addressed beauty related vocabulary in general terms, leaving a gap in focused analysis of “漂亮” as an independent and multifunctional evaluative unit. In particular, its semantic expansion beyond physical appearance into abstract domains such as work quality and success remains insufficiently systematized.The study employs descriptive and semantic analysis based on examples from everyday spoken Chinese and contextual usage patterns. Through qualitative examination, the research identifies core meanings, pragmatic features, and extended metaphorical uses of the word.The findings show that “漂亮” functions as a balanced and neutral evaluative adjective that expresses not only external aesthetic appeal but also effectiveness, precision, and successful outcomes. Its semantic extension reflects broader shifts in how beauty is conceptualized in modern Chinese society.The results highlight the close relationship between linguistic change and evolving social values. This study contributes to Chinese lexical semantics and offers practical implications for language teaching, intercultural communication, and discourse analysis by clarifying how aesthetic evaluation operates in contemporary Chinese usage.